Penguatan Kompetensi Riset Mahasiswa melalui Pelatihan Proposal Penelitian - Tania Pratiwi, Rani; Suryani, Yeyen; Jumantini, Entin; Dandi, Dandi; Maryati, Meri (DEDIKASI: Jurnal Pengabdian kepada Masyarakat, 2026)
Academic literacy constitutes the foundational scientific competency of university students in higher education; however, a substantial proportion of final-year students continue to experience significant difficulties in composing research proposals that conform to established academic standards. This community service initiative represents the outcome of a collaborative endeavour between Taman Pelangi of Bayuning Village and the Economic Education Student Association of Universitas Kuningan, materialised in the form of a Research Proposal Writing Training programme. This activity constitutes part of Activity-17 of Taman Pelangi, which aims to enhance students' academic literacy competencies through an intensive training approach grounded in peer-review mechanisms and direct mentorship. The implementation methodology encompassed two sessions: an offline session comprising interactive face-to-face instruction and an online session involving guided assignments for proposal refinement. The programme was attended by 12 participants drawn from students in the fifth and seventh semesters. The outcomes of the activity demonstrated a significant improvement in the quality of proposal manuscripts, as evidenced by the participants' ability to formulate problem backgrounds grounded in research gaps, construct measurable research questions, and select methodologically appropriate approaches. The peer-review mechanism was demonstrated to effectively cultivate a culture of critical and collaborative thinking. This activity recommends the cross-institutional collaboration model as an effective paradigm for community service initiatives aimed at strengthening students' academic capacities.